Pengaruh Good Corporate Governance, Firm Size, Dan Divident Payout Ratio Terhadap Financial Performance Dan Firm Value Pada Perusahaan Indeks Lq45 Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2018 – 2024 - Rahayu, Pinta Rohmada; Dananjaya, Yanuar (Syntax Literate, 2025)
It aims to provide insights for investors in evaluating Firm Value and for management in enhancing financial performance. The sample was selected using purposive sampling. Data analysis included outlier detection, classical assumption testing, and both simultaneous and partial effect testing. The independent variables—Independent Board, Board Size, and Insider Shareholding—were analyzed to assess their impact on Firm Value and Financial performance, while Firm Size and Divident Payout Ratio were treated as control variables. Findings reveal that Insider Shareholding, Independent Board, and Firm Size significantly influence Firm Value, whereas Board Size and Divident Payout Ratio do not. In contrast, Insider Shareholding, Board Size, Firm Size, and Divident Payout Ratio significantly influence Financial performance, while Independent Board has no effect.